Ratio of Platelet-Limfosites and Leukosit Level as Indicators of Baby Feedback (APGAR Score) on Premature Rupture of Membrane Cases iIn Ulin General Hospital - Wibowo, Yuvens Richardo (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: Premature rupture of membranes (PROM) has the potential effect to cause complications such as premature infants, neonatal sepsis, and intrauterine infection (chorioamnionitis). Some inflammatory markers have been investigated to detect PROM at their early stage and prevent the complications. Platelet lymphocyte ratio (PLR) and leukocytes are a simple, affordable inflammatory marker, and have been used to predict a variety of inflammatory conditions. This study aims to see the relationship between PLR and leukocytes with APGAR Score in the case of PROM. This study was an analytic observational study with a retrospective cross sectional design. Data from 80 samples showed PLR and leucocytes had no significant effect on APGAR value (p> 0.05).Â Keywords: Platelet Lymphocyte Ratio, Premature rupture of membranes, APGAR score